An enemy of the people - IBSEN, Henrik; O'Brien, Jack, 1939-; Miller, Arthur, 1915-2005; Glover, John, 1944-; Grizzard, George; Mahaffey, Valerie; Ibsen, Henrik, 1828-1906.; LC Off-Air Taping Collection (Library of Congress) (Nairobi: East African Educational Publishers, 2001)
In Riverton, Maine, circa 1893, Dr. Thomas Stockman wants to disclose that the town's moneymaking health spa "Clearwater Springs" has been fouled by pollution from a tannery. But his proposal to go public is opposed by his brother Peter, the town mayor, who prompts a wave of public outrage against Dr. Stockman and his family.
Copyright: no reg.
Copyright notice on film: Community Television of Southern California ; 1990.
Summary taken from TV guide (New York metropolitan edition).
Number referring to episode on accession card for off-air tape viewing copy is number 908.
Based on the play, [En Folkefiende], by Henrik Ibsen.
A conversation with Arthur Miller and Jack O'Brien immediately follows American playhouse presentation.
Keywords: African Literature; Adaptation -- Anthology -- Television series